Ventajas competitivas de sector panelero colombiano, tomando como referencia la dinámica del mercado entre 2015- 2019 (2021)
Taking into account that Panela is a representative product of Colombia, followed by Coffee, this research work considers important to recognize Porter's five forces in order to identify how the state of El sector Panelero in our country is. To do that, the dynamics between 2015 – 2019 were addressed and different advantages and disadvantages were discovered. The method used to this research process was inductive-descriptive, with a Documentary Historical approach. After collecting and analyzing the data,